EFFECTS OF A RESISTANCE TRAINING WITH ELASTIC TUBING IN STRENGTH, QUALITY OF LIFE AND DYPSNEA IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Bruna Spolador de Alencar Silva; Luis Alberto Gobbo; Ana Paula Coelho Figueira Freire; Iara Buriola Trevisan; Isis Grigoletto Silva; Ercy Mara Cipulo Ramos (Journal of Physical Education)
ABSTRACT The objective of this study was to analyze the effects of resistance training with elastic tubes and weight machines (conventional) on muscle strength, quality of life and dyspnea in patients with chronic obstructive pulmonary disease (COPD). Patients were allocated in training groups with elastic tubes (ETG, n = 9) and conventional (CRG, n = 10) and evaluated by isometric strength and quality of life questionnaire (CRQ) and dyspnea (MRC). Isometric strength increased by ~25% in both groups in all movements (p <0.05). MRC and the CRQ dyspnea domain showed improvement of -28.70% and -6.05% in the ETG, and -33.33% and -16.23% at CRG, respectively. Shoulder and elbow flexion showed a negative and significant correlation with MRC (p <0.05), for CRG. Both interventions were beneficial for increasing the strength and reducing the MRC score, and increased strength of upper limbs correlated to the reduction of the sensation of dyspnea in patients with COPD.